Kepemimpinan Transformasional dan Quality Of Work Life terhadap Komitmen Organisasi Melalui Kepuasan Kerja - Azul Aidin; Hafriz Rifki Hafas; N Nurhaliza (JaManKu: Jurnal Manajemen dan Kewirausahaan, 2022)
This study aimed to examine and analyze whether transformational leadership and quality of work life partially affect employee job satisfaction. To test and analyze whether transformational leadership, quality of work life, and job satisfaction partially influence organizational commitment. To test and analyze whether job satisfaction intervenes with transformational leadership and quality of work life on organizational commitment. The total population in this study was 100 people in the planning division, and all of them were taken as samples using saturated sampling. The analysis technique used is path analysis. The results showed that transformational leadership had no significant effect on organizational commitment, quality of work life had no significant effect on organizational commitment, job satisfaction had a significant effect on organizational commitment, transformational leadership had a significant effect on job satisfaction, quality of work life had a significant effect on job satisfaction. Then transformational leadership had a significant effect on organizational commitment through job satisfaction and quality of work life had a significant effect on organizational commitment through job satisfaction, so this indicates an indirect effect.